Kenaf core fibre/unsatured polyester resin biocomposites: Effect of fibre loading on mechanical and physical properties - Umi Kalsum Binti Jamal Mohamed (2023)
In this study, biocomposites reinforced with kenaf core fibre (KCF) and unsaturated polyester resin (UPE) were made using a hand lay-up and compression moulding process. The goal of the study was to find out how KCF loading affected the mechanical and physical characteristics of UPE biocomposites. The bending test and the water absorption test, respectively, were used to describe the mechanical and physical properties of the KCF-UPE biocomposites. As the number of fibres grows, the rate of water absorption decreases. The findings indicate that when KCF level increased, the flexural strength reduced. Flexural strength of the KCF/UPE biocomposites first showed a minor decline at UK10 KCF incorporation before abruptly increasing with greater loading. Flexural modulus, on the other hand, rises at UK5, falls at UK10, and then dramatically rises at UK15. Keywords: kenaf core fibre, unsatured polyester resin, mechanical properties, physical properties, water absorption, flexural strength, flexural modulus